2021
DOI: 10.3332/ecancer.2021.1220
|View full text |Cite
|
Sign up to set email alerts
|

Survivor and parent engagement in childhood cancer treatment in Iran

Abstract: In Iran (with a population of 83 million), 19,973 children were diagnosed with cancer from 2009 to 2019 (MAHAK Charity). This study was part of the International Society of Paediatric Oncology, Paediatric Oncology in Developing Countries Committee, 'Patient, Family and Stakeholder Engagement Task Force' engagement study in ten low-and middle-income countries in 2019. We documented childhood cancer survivors and parents' experiences and quality of engagement, including perceptions and expectations, during their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Factors related to professional interaction and communication were described in 25% of articles 45,46,49–51, 54–56,61,62,65–88 . Factors related to professional interaction and communication in articles that focused on the perspective of patients and families included the invitation to participate in decision‐making, 54,62,65,70,88 trust, 70,73,81 or distrust 49,51,86 in their healthcare providers, variable quality of patient‐healthcare team communication, 79,86,87 including disempowerment of patients, lack of patient understanding of therapy or therapeutic options, and fear of raising questions risking the potential for inferior care 87 . Additional factors included deliberate miscommunication to convince a patient to accept care, 87 time constraints of the physician, 49,50,68 and language barriers that prevented the effective description of cancer and cancer therapies with patients and families 87 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors related to professional interaction and communication were described in 25% of articles 45,46,49–51, 54–56,61,62,65–88 . Factors related to professional interaction and communication in articles that focused on the perspective of patients and families included the invitation to participate in decision‐making, 54,62,65,70,88 trust, 70,73,81 or distrust 49,51,86 in their healthcare providers, variable quality of patient‐healthcare team communication, 79,86,87 including disempowerment of patients, lack of patient understanding of therapy or therapeutic options, and fear of raising questions risking the potential for inferior care 87 . Additional factors included deliberate miscommunication to convince a patient to accept care, 87 time constraints of the physician, 49,50,68 and language barriers that prevented the effective description of cancer and cancer therapies with patients and families 87 …”
Section: Resultsmentioning
confidence: 99%
“…One study described gender bias in the treatment of osteosarcoma and the neglect of female patients 66 . Other factors included treatment toxicities, 46,48,49,51,53,54,56,57,63,66,70,74,79,80,85,87,89,93,98,100–103 specific disease features, 50,51,56,57,59,64,76,77,80,96,98,104 the results of diagnostic workup, 65,75,77,80 and access to cancer‐directed treatment and supportive care resources and personnel 46,49–51,54–56,61,62,65,66,68,70,73–75,77,78,80–84,86–88,94,98,102–105 …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, previous studies have shown that parents expected to know the facts about their child's illness. Parents are confused when their child is diagnosed with cancer, and constantly search for information about the disease type, treatment, and outcome (Moridi et al, 2018;Ahmadnia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…14 Thirty-two hospitals provide pediatric cancer care under the supervision of medical universities; however, national guidelines are lacking. 15 Treatment costs are covered by a few health care insurance companies and nongovernmental organizations (NGOs). 16 According to GLOBOCAN 2015, of 1567 children diagnosed with cancer, 66% died.…”
Section: Introductionmentioning
confidence: 99%
“…The age‐standardized incidence rate of childhood cancer under the age of 15 is 11.9/100,000 14 . Thirty‐two hospitals provide pediatric cancer care under the supervision of medical universities; however, national guidelines are lacking 15 . Treatment costs are covered by a few health care insurance companies and nongovernmental organizations (NGOs) 16 .…”
Section: Introductionmentioning
confidence: 99%